Antanas Matulevičius and his Petersburgs “Textbook of Arithmetic” - Banionis, Juozas (Lietuvos matematikos rinkinys, 2011)
A. Matulevičius is one of the graduates of Veiveriai Teachers’ Seminary who became known for writing textbooks of mathematics in Lithuanian. His two-part “Textbook of Arithmetic” (Petersburg, 1916) was designed for teaching operations with numbers from first decade till one thousand. In the textbook he also introduced fractions and operations with them. Textbook material was presented concentrically to follow a method of  purposeful tasks. Thus, the textbook included a great deal of practical tasks. Although only several of the terms given in the textbook became officially used in the Lithuanian language, they reflect historical development of the creation of Lithuanian terminology and are important from this point of view.
Keywords: Veiveriai Teachers’ Seminary; primary course of arithmetic; operations with numbers; fractional; operations name